The Village Head's Strategy to Enhance Social Inclusion in Bulo-Bulo Village Pujananting District Barru Regency - M, A. Pananrangi; Marsuki, Marsuki (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research aims to analyze the strategies implemented by the Village Head to enhance social inclusion in Bulo-Bulo Village, Pujananting District, Barru Regency. The research methodology utilized is qualitative research with a case study approach. Data were obtained through in-depth interviews with the Village Head, community leaders, and other stakeholders in the village. The results of the study indicate that the Village Head has implemented various effective strategies to improve social inclusion in Bulo-Bulo Village. These strategies include enhancing accessibility to public services, developing inclusive infrastructure, empowering the community through training programs and skill development, and utilizing information technology to expand communication and information dissemination. The implementation of these strategies has had a significantly positive impact on the level of social inclusion in Bulo-Bulo Village. There has been an increase in community participation in social and economic activities, improved access to healthcare and education services, and heightened awareness of the importance of social inclusion in village development. Based on the research findings, it is concluded that the strategies employed by the Village Head to enhance social inclusion in Bulo-Bulo Village can serve as a relevant model for application in other areas. Cooperation among local governments, communities, and the private sector is necessary to support the broader and sustainable implementation of social inclusion strategies across various regions in Indonesia.